Is 35 U.S.C. § 271(F) Keeping Pace With The Times?: The Law After the Federal Circuit’s Cardiac Pacemakers Decision - Shuttleworth, Lauren (Journal of Law and Commerce, 2010)
In a common business arrangement, an American software company designs software in the United States, then sends the software code abroad where copies are mass-produced and distributed. Prior to the Federal Circuit’s ruling in Cardiac Pacemakers, Inc. v. St. Jude Medical, Inc., the American company could have been found liable for patent infringement under Section 271(f) of the Patent Act if the software mass-produced abroad infringed a United States patent.Cardiac Pacemakers, however, leaves United States patent owners defenseless when the allegedly infringed patent claims are method claims. The background of Cardiac Pacemakers, the Court’s rationales, and the implications of the decision are the subject of this Note.